General relativistic nonideal fluid equations for dark matter from a truncated cumulant expansion - Erschfeld, Alaric; Flörchinger, Stefan; Rupprecht, Maximilian (Physical review, 2020)
A new truncation scheme based on the cumulant expansion of the one-particle phase-space distribution function for dark matter particles is developed. Extending the method of moments in relativistic kinetic theory, we derive evolution equations which supplement the covariant conservation of the energy-momentum tensor and particle number current. Truncating the cumulant expansion we obtain a closed, covariant and hyperbolic system of equations which can be used to model the evolution of a general relativistic nonideal fluid. As a working example we consider a Friedmann-Lemaître-Robertson-Walker cosmology with dynamic pressure and solve for the time evolution of the effective equation of state parameter.
Gesehen am 26.10.2020